The Identification of a Novel Highly Condensed Pentacyclic Heteroaromatic Ring System 1, 3, 5, 5b, 6, 8, 10, 10b‐Octaazacyclopenta[h, i]Aceanthrylene and its Application in the Synthesis of 5, 7‐Substituted Pyrazolo[4, 3‐d]Pyrimidines. (29th May 2014) - Havlíček, Libor; Moravcová, Daniela; Kryštof, Vladimír; Strnad, Miroslav
<x xml:space="preserve">Abstract</x> Pyrazolo[4, 3‐d]pyrimidines are of interest as potential kinase inhibitors. This article describes the formation of a novel highly conjugated, condensed, centrosymmetric heteroaromatic compound, 4, 9‐dichloro‐2, 7‐diisopropyl‐1, 3, 5, 5b, 6, 8, 10, 10b‐octaazacyclopenta[h, i]aceanthrylene (3), during the chlorination of 5, 7‐dihydroxypyrazolo[4, 3‐d]pyrimidine (1) with phenylphosphonic dichloride. The nucleophilic attack of benzylamine on 3 afforded N‐benzyl‐5‐chloro‐3‐isopropyl‐1H‐pyrazolo[4, 3‐d]pyrimidin‐7‐amine (6), which was further substituted to yield a pyrazolo[4, 3‐d]pyrimidine analogue of roscovitine, a well‐known cyclin‐dependent kinase inhibitor.